"Explain it on the blackboard". An analysis of the educational interaction in mirror assessment activities. (September 2019) - Montanero, Manuel; Marques, Maria-João
Highlights: Social interaction is organized in Initiation-Response-Evaluation/Feedback sequences. Succession of inquiry-based questions is the main verbal device. Target students actively participated in the assessment and even self-corrected. Verbal interaction with observers does not reflect conditions of formative assessment. Some teachers used three dialogic strategies in order to encourage episodes of discussion.